Psychological Impact of Acne and its Homoeopathic Management (Homoeopathy for All, 2022)
Acne is one of the most familiar  skin complaints encountered by  millions of people of all ages,  colours and skin types.1 For many  suffering from acne seems a never ending process. It is estimated that  more than 85% of adolescents suffer  from it and it extends into adulthood  in approximately.2 50% of cases.  The location (on the face) the acne  appears, make it more troublesome  for the sufferer. Research suggests  that acne affects mental health  and leads to anxiety, stress,  depression, poor self-confidence  and social isolation. As per the  recent studies in the dermatology  clinic, 25%-43% of patients visit  have a psychological disorder.3,4 The comorbidity of depression  and skin diseases is around 30%.5 The study also found that stress is  one of the aggravating conditions  of skin diseases.6 Conventional  treatments have limited scope in  the management of acne. Usually,  they focus on inhibiting sebum  production, limiting bacterial  growth, encouraging the shedding  of skin cells to unclog pores, or a  newer treatment that blocks male  hormones in the skin. It is known to  all that such treatment has long-term  side effects. In this article, we have  focused on the association of acne  with psychology and the efficacy  of homoeopathy treatment in the  management of acne along with the  change in the quality of life.
Keywords: adulthood; anxiety; homoeopathy